Dynamics of the prevalence of chronic alcoholism in Odesa region during the COVID-19 pandemic - Goncharov, Віталій; Bondarenko, Дмитро; Dementiev, Сергій; Varetska, Олена; Potienko, Лариса; Maksymenko, Юлія (Psychosomatic Medicine and General Practice, 2022)
This text is the thesis of the 3rd congress with international participation "Psychosomatic medicine of the 24th century: realities and prospects". The following is devoted to the study of the dynamics of the prevalence of chronic alcoholism in the Odesa region during the COVID-19 pandemic.